Estudio de la Gestión de la Empresa Pública Municipal “Gestión y Desarrollo” (Gedes) de la ciudad de Loja, año 2022 - Torres Rojas, Melania del Carmen (2024)
The “Study of Management of the Municipal Public Company “Management and Development” (GEDES) of the city of Loja in the year 2022” examined the management quality in relation to the services or goods that the company provides to the citizens of Loja with the aim of directing strategic sectors for the benefit of the citizens, based on the ease of investing in economic resources and surpluses in executing projects generating profits for both citizens and the State, it may in certain instances be wholly or partially owned by the State. The approach of this work was done through a general objective that focuses primarily on the “Study of the management of the Municipal Public Company “Management and Development” (GEDES) of the city of Loja during the year 2022” and its development was done through specific objectives focused on “Diagnose the current state of the management of the Municipal Public Company "Management and Development” (GEDES) of the city of Loja”, and “Identify Strategies to improve the Management of the Municipal Public Company Management and Development (GEDES) of the city of Loja”. Moreover, qualitative and quantitative information regarding the company's management was collected using interview techniques, surveys, observation sheets and focus groups. Data from the surveys and interviews were analyzed using inductive, analytical and synthetic methods. As a result of analyzing the theoretical framework and summarizing the most relevant research information, we were able to obtain an understanding of the success and development of the projects, the deficiencies present in certain areas of both the company and the projects, and finally the recommendations that were made regarding the implementation of strategies to alleviate the problems.